Analysing role transitioning from functional specialist to leadership: A case study of a media development agency - Nompumza, Sisanda, James (Rhodes University, Faculty of Commerce, Rhodes Business School)
The study explored the role transition experiences of media development agency employees transitioning from functional specialists to leadership roles. Role transitions can pose significant challenges, which can adversely affect individual performance and organisational effectiveness. Challenges included identity transformation, role conflict, role ambiguity, and role overload. The study used a qualitative case study design, collecting data through semi-structured interviews from eight managers who transitioned from functional specialist roles to leadership roles. Thematic analysis was conducted to organise the data and identify thematic patterns and themes that emerged from their experiences. The results indicated that participants faced challenges associated with competing priorities; balancing the responsibilities of their former responsibilities and new role as a leader; ambiguous expectations in the new role; and ambiguity connected to a fast-paced and overwhelming workload. Organisational supports, such as mentorship programs, onboarding and continual development programs, the provision of mentors for professional development, and security provisions, were essential for managing transitions. Participants were able to create adaptive coping mechanisms, including self-directed learning and personal networks, to engage with peers in leadership roles. The research provided theoretical and practical insight into role transitions, which were beneficial in generating new actionable recommendations for the public sector organisations looking to improve their leadership development initiatives. While the study is exploratory with limitations for generalisability, it has opened space for future research in role transitions, which could include a longitudinal study of leadership transitions into new roles, comparative studies of public sector institutions, and an exploration of female and male issues in role transition experiences.
Keywords: Uncatalogued